Historic doubts, conjectures, and the wanderings of a principal curiosity: Henry VII in the fabric of Strawberry Hill. Issue 3 (3rd July 2017) - Calè, Luisa
Abstract: This article explores the inscriptions and material metamorphoses of Henry VII in Horace Walpole's 'paper fabric', a reversible world of writing, collecting, and book-making. In Anecdotes of Painting in England (1762), Walpole celebrates the funerary monument of Henry VII by Pietro Torrigiano at Westminster Abbey. In Historic Doubts on the Life and Reign of King Richard the Third (1768), conjecture and speculation become methodological prompts to unveil the textual and architectural discontinuities of history. Walpole's next historical experiment consists in placing a bust of Henry VII in the agonies of death in the Star Chamber at his house at Strawberry Hill in Twickenham. The bust's importance is captured by its reappearance propped on top of a frontispiece and its dissemination in other reproductions in extra-illustrated copies of A Description of the Villa of Mr. Horace Walpole, Youngest Son of Sir Robert Walpole Earl of Orford, at Strawberry-Hill near Twickenham, Middlesex … (1784). A dramatic representation of the bust in John Carter's extra-illustrated copy of A Description, later engraved in his Specimens of the Ancient Sculpture and Painting now remaining in this Kingdom (1780–94), shows the alternative trajectories of Henry VII from Westminster Abbey to Strawberry Hill, from Walpole's cosmopolitan collection of curiosities to Carter's paper collection of national gothic specimens